A Classroom Action Research (CAR): Students’ Creativity Enhancement Through Problem Solving Learning - Wanda Nugroho Yanuarto (Universitas Tidar, 2020)
The purpose of this study is to improve students’ creativity through problem solving learning. Students’ creativity is an important issue in Mathematics Economics class. Some of the problems that occur are (1) the lack of students in asking questions; (2) low idea of students; (3) lack of courage in expressing opinions; (4) lack of ability to solve difficult mathematical problems in class, and (5) ) lack of courage in defending his opinion when discussing. This research is a classroom action research on mathematics economics course in Mathematics Education Department, University of Muhammadiyah Purwokerto in 2018/2019 academic year. The research phase includes (1) planning, (2) implementing actions, (3) observation, and (4) reflection. The results of this study show good results, because of the 55 students, only 3 students who scored less in the category and the second cycle only 1 student who scored less. Therefore, it can be concluded that problem solving learning can enhance students’ creativity.